2006
DOI: 10.1021/jp065003y
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry of Acetonyl and Related Radicals

Abstract: Density functional and ab initio calculations at CBS-QB3 levels of theory were employed with a series of isodesmic reactions to determine the thermochemistry of the 2-oxopropyl or acetonyl radical (CH(3)COC*H2). In turn, this was used to determine formation enthalpies of 2-oxoethyl or formylmethyl (C*H(2)CHO), 2-oxobutyl (C*H(2)COC(2)H(5)), 1-methyl-2-oxopropyl or methylacetonyl (C*H(CH(3))COCH(3)), 1-methyl-2-oxobutyl (C*H(CH(3))COC(2)H(5)), and 3-oxopentyl (C*H(2)CH2COC(2)H(5)). Our computed standard enthalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 79 publications
4
41
0
1
Order By: Relevance
“…Acetonyl has a partially delocalized electronic structure that may be portrayed by the limiting "alkyl", •CH 2 C(=O)CH 3 , and "alkoxyl", CH 2 =C(-O•)CH 3 , resonance structures [17], [18].…”
Section: Reactivity Of the Acetonyl Radicalmentioning
confidence: 99%
See 2 more Smart Citations
“…Acetonyl has a partially delocalized electronic structure that may be portrayed by the limiting "alkyl", •CH 2 C(=O)CH 3 , and "alkoxyl", CH 2 =C(-O•)CH 3 , resonance structures [17], [18].…”
Section: Reactivity Of the Acetonyl Radicalmentioning
confidence: 99%
“…The long established standard enthalpy of formation of acetonyl, ∆ f H°2 98 (CH 3 C(O)CH 2 ) = -23 ± 8 kJ mol -1 , was proposed by King et al by kinetic study of the gas-phase bromination of acetone [5], while the recent reports converge to a value which is ~10 kJ mol -1 smaller (a thorough overview of the literature has been presented in [18]). The critically evaluated, recommended value is ∆ f H°2 98 (CH 3 C(O)CH 2 ) = -34 ± 3 kJ mol -1 [10].…”
Section: Thermochemical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since enthalpies of formation of the three reference compounds (values above in bold) are well established [40] in the literature, the heat of reaction, rxn H…”
Section: Enthalpies Of Formation ( F298 Hmentioning
confidence: 99%
“…Mixtures of 80% kerosene and 20% FAMEs were widely considered as a possible option to be used in aviation; however, because of the physical properties of FAMEs and their levels of metallic contaminants, this is no longer an acceptable option and, in practice, only synthetic Fischer Tropsch derived fuels have a future as a kerosene replacement. Few studies have investigated the oxidation chemistry of oxygenated compounds, such as acetic and propanoic acids [3,4], followed by detailed chemical reaction mechanisms for small fatty acid methyl esters as biofuel surrogates [5][6][7][8][9][10]. Dagaut et al [11] developed a model for the combustion of biokerosene, basing it on previous studies [12], which showed that the biofuel portion (typically rapeseed methyl esters (RME)) could be well represented by hexadecane.…”
Section: Introductionmentioning
confidence: 99%